Identifying Parties of Support System to Prevent Suicide Behavior of Adolescents - Alfrojems Alfrojems; Kanya Eka Santi; Chairani Chairani (Asian Social Work Journal, 2019)
Suicide cases are a worldwide phenomenon, especially if the perpetrators of suicide are Adolescents, so it is not surprising that 7 (seven) suicides committed by adolescents in Dompu Regency, West Nusa Tenggara Province, Indonesia are an interesting case to explore and traced. This article aims to explore information about suicidal behavior in adolescents, especially in the area of Dompu Regency, West Nusa Tenggara Province. The research method in this article is qualitative with descriptive type. The results of this study indicate that there are a number of conditions that cause adolescents in Dompu regency to become vulnerable in committing suicide, this is also followed by quite strong reasons. In addition, this study also succeeded in exploring several parties who were able to play a role in preventing suicide behavior in adolescents. The recommendations presented in this article are the need to strengthen support through educational institutions that involve peers to provide support to other adolescents so as to be able to find solutions to any problems experienced and be able to prevent suicidal behavior in adolescents.